Futuro do pretérito : do patrimônio vivido ao patrimônio tombado na Cidade de Goiás 2000/2021 - Silva , Pedro Augusto Diniz (2022)
This is a study that seeks to understand the course of two decades of the recent history of the Cidade de Goiás. This path begins when a part of this community mobilized to demand and to receive the most important patrimonial recognition title, Humanity´s Cultural Heritage, in 2001, and ends with the Pandemic period of Covid-19, 2020 to nowadays. Using as a reference the popular participation in annual celebrations of their religious traditions. I tried to identify the projection to the future that the Vilaboense people to do to their community, their expectations, their frustrations, and demands from this received. Highlighting the cultural socio-economic division between the recognized urban polygon as a heritage of humanity and the adjacent region that feels discriminated against managers and their local policies. The results of this analyses and study was the elaboration of a documentary called: “Futuro do pretérito: entre diálogos pratimoniais”. The Goiás city will complete 300 years of urban occupation in 2027, and, that´s why I considered the pertinence of this theme and in reason of the extensive professional activity of researcher that I exercise in this community. As well my heritage film productions as over these 2 decades, I used as research support the collection of moving images generated during that time, as much as a starting point and reference for the development of actions in the field, recording interviews and application of forms. I tried to articulate the material and cultural factors in these social analyses, being identified the recurring conflicts of interest in power disputes (Centro histórico x Periferia) in the dynamic trajectory of the constitution of collective memory.